Risk-based flight planning and management for urban air mobility - Su, Yu; Xu, Yan (AIAA, 2022)
This paper investigates a quantitative ground risk assessment method for future urban airmobility, which can be divided into three main processes: risk modelling, risk assessment andmitigation recommendation for flight planning and management. First, the aircraft kineticmodels for both fixed-wing aircraft and rotorcraft are investigated, along with the correspondingballistic and glide descent mode and the associated wind influence. The probabilistic impact toroad traffic and pedestrians on the ground as a result of potential crash are then derived. Withan assumed crash probability of the aircraft, the initial risk value and distribution are computed,which are used to produce a risk cost map across the mission area. Next, the flight request isprocessed based on such risk map using a common path planning algorithm, minimizing theoverall risk for the flight plan to be generated. Finally, a preliminary case study involving arotorcraft conducting urban cargo transportation service is performed to evaluate the proposedrisk assessment method in a real-world urban environment.
Keywords: Air Transportation Systems